Traders Perception and Behavior in Weighing (in Terms of Q.S. Al-Muthaffifin) - Nabil Shawab al-Mujaddid; Azhari Akmal Tarigan; Muhammad Ramadhan (ITB AAS INDONESIA Surakarta, 2022)
This article examines traders perceptions and behaviors when it comes to weighing merchandise. The importance of this research stems from the fact that many traders still cheat their scales today. Cheating on the scales appears to be a common practice in trading because it is the result of classical economic thinking, namely taking as much profit as possible. At this level, the author examines the perceptions and behavior of traders in the Pusat pasar Medan when it comes to weighing their goods. The author uses surah al-Muthaffifin as a reference to describe the perceptions and behavior of traders according to Islamic standards in order to determine the main idea. Surah al-Muthaffifin was chosen as a reference because there are values in Islamic trading that are related to ethics and social values. This research employs a qualitative approach with a phenomenological approach. In this article, data collection techniques such as interviews and observations are used to generate raw data, which is then processed using data analysis techniques to ensure validity. The perceptions and behaviors formed in Surah al-Muthaffifin regarding weighing merchandise are actually quite well understood, however, perceptions are not fixed, so there are a variety of factors that can damage these perceptions. In reality, Pusat Pasar traders understand and adhere to trading ethics, though there are some traders who disregard the ethics, particularly when weighing.